Development of a windmill for pumping water using positive displacement pump - Alkali, B.; Elkanah, B. S.; Amarem, S. G.; Hassan, A. B.; Gukop, N. S.; Egbe, E. A. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
The abundant renewable energy sources have not been harnessed for electricity and other uses to date. Wind speed is high in the Northern part of Nigeria and therefore require utilization so as to reduce the use of harmful non-renewable energy sources. In this work wind energy was used to drive a windmills that provide mechanical energy directly for a borehole with a positive displacement pump with a 2.5ft stroke. The design analysis of the wind mill was carried out numerically based on the wind data collected. The proposed design were fabricated using designed dimensions. The rotary motion of the shaft were converted to a linear motion using slider-crank mechanism. The designed horizontal axis windmill has 3 blades has three blades driving the shaft. Also the kinematic modelling of the mechanism was carried out. The assembled windmill was tested and was found to have an operated efficiency of 58.2%.